Molecular Advances in Wheat and Barley - Martinez, Manuel (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Allohexaploid bread wheat and diploid barley are two of the most cultivated crops in the world. This book reports novel research and reviews concerning the use of modern technologies to understand the molecular bases for wheat and barley improvement. The contributions published in this book illustrate research advances in wheat and barley knowledge using modern molecular techniques. These molecular approaches cover genomic, transcriptomic, proteomic, and phenomic levels, together with new tools for gene identification and the development of novel molecular markers. Overall, the contributions for this book lead to a further understanding of regulatory systems in order to improve wheat and barley performance.